The open academic robot kit - Sheh, Raymond; Eguchi, A.; Komsuoglu, H.; Jacoff, A. (2017)
© Springer International Publishing AG 2017. All rights reserved. The Open Academic Robot Kit (OARKit) lowers the barrier of entry into robotics research. A community-driven initiative, it was developed in the context of the RoboCupRescue Robot League competition to advance the state of research in response robotics. All mechanical parts are 3D printable, available off the shelf and/ or, ideally, drawn from a set of common parts. All designs, instructions and source code are available online in easily editable form under an open-source licence. These principles allow the OARKit robots to become powerful tools to encourage collaboration across regions, generations and areas of expertise. The principles that govern this initiative can be applied broadly to other robotics applications that require interdisciplinary skills in order to build complete, useful, interesting research implementations.